Hepatitis A virus age‐specific sero‐prevalence and risk factors among Jordanian children. Issue 4 (3rd February 2015) - Hayajneh, Wail A.; Balbeesi, Adel; Faouri, Samir
<x xml:space="preserve">Abstract</x> Hepatitis A Virus (HAV) has been a significant cause of infections among the children and adolescents of Jordan. Availability of safe vaccines made it necessary to identify the ill‐defined temporal immunity trends for HAV and possible age‐specific prevalence transitions. This community‐based cross sectional study was conducted during the period July–August 2008 on 3, 066 recruited subjects from the 12 governorates of Jordan, with pre‐defined criteria. Several households were chosen at random within each selected block to enroll the subjects. They were interviewed and data were collected. Their sera were tested for total antibodies against HAV. A multivariate model was then performed to identify the possible risk factors. The HAV sero‐prevalence rates among the age categories—second year, 2–4 years, 5–9 years, 10–14 years, 15–19 years, and those above 20 years were 26%, 32%, 44%, 63%, 78%, and 94%, respectively. The model revealed the association of several risk factors for higher HAV sero‐prevalence rates: (i) older age groups; (ii) lower maternal education levels; (iii) residing in certain governorates; (iv) using public net drinking water; and (v) avoiding use of public net sewage system. This study provided strong evidence for continuous transition of HAV epidemiology towards intermediate endemicity in Jordan, with more susceptible adolescents and adults. Following the World Health Organization (WHO) recommendations for countries with intermediate endemicity, large‐scale hepatitis A vaccination is recommended for children in Jordan. This is strengthened by the availability of effective and safe HAV vaccines, improving the socio‐economic status of the Jordanians, and increasing life expectancy among Jordanians. J. Med. Virol. 87:569–574, 2015. © 2015 Wiley Periodicals, Inc.